Retrospective evaluation of the effectiiiveness a modern method for stopping hypotonic uterine bleeding in the early postpartum period - Gaidai, N. V.; Oliynyk, N. S.; Revenko, O. M.; Гайдай, Наталія Вікторівна; Олійник, Наталія Сергіївна; Ревенько, Олександр Мойсейович (Запорізький державний медичний університет, 2020)
Contemporary statistics from WHO suggests massive obstetric bleeding stands in 2nd place in the list of causes for maternal mortality in Ukraine and is evident that, more than 20% of maternal deaths are related to it. As a solution, application of uterine balloon tamponade(UBTM) is suggestive, on application, the Postpartum hemorrhage(PPH) diminishes by 2.5 times.
Keywords: massive obstetric bleeding; postpartum hemorrhage; controlled uterine balloon tamponade (UBTM); uterine activity; infertility problems